PENYEDERHANAAN RITUAL SEBAGAI ALTERNATIF BERAGAMA HINDU DI ERA SAAT INI - Suarjaya, I Wayan (PANGKAJA: JURNAL AGAMA HINDU, 2018)
The simplification of the ceremony is an issue that is being discussed by both intellectuals and the gen- eral public. They are discussing this because it allegedly burdens the community in the midst of today?s fast-paced life. Changes in the times demand that every Balinese person must devote more time to the profession so that very little can be used for the community. Not to mention the basic needs currently increasing which previously did not include counts, such as tuition fees, transportation costs, commu- nication costs, and other types of costs that were initially tertiary and secondary, turned into primary needs. Meeting these many needs, they objected to the expensive ceremony fees. Not a few of them must be willing to give up their inheritance to sell or seek debt only for the sake of yadnya. This work describes the urgency, who plays a role in the effort and how simplification can occur. In this discussion, the tri aspect of dating the yadnya is very important, namely the pandita who presides over the ceremony, the tapini who works the ceremony and the yajamana who holds the ceremony.